A non-canonical role of somatic Cyclin D/CYD-1 in oogenesis and in maintenance of reproductive fidelity, dependent on the FOXO/DAF-16 activation state. - Umanshi Rautela; Gautam Chandra Sarkar; Ayushi Chaudhary; Debalina Chatterjee; Mohtashim Rosh; Aneeshkumar G Arimbasseri; Arnab Mukhopadhyay (PLoS Genetics)
For the optimal survival of a species, an organism coordinates its reproductive decisions with the nutrient availability of its niche. Thus, nutrient-sensing pathways like insulin-IGF-1 signaling (IIS) play an important role in modulating cell division, oogenesis, and reproductive aging. Lowering of the IIS leads to the activation of the downstream FOXO transcription factor (TF) DAF-16 in Caenorhabditis elegans which promotes oocyte quality and delays reproductive aging. However, less is known about how the IIS axis responds to changes in cell cycle proteins, particularly in the somatic tissues. Here, we show a new aspect of the regulation of the germline by this nutrient-sensing axis. First, we show that the canonical G1-S cyclin, Cyclin D/CYD-1, regulates reproductive fidelity from the uterine tissue of wild-type worms. Then, we show that knocking down cyd-1 in the uterine tissue of an IIS receptor mutant arrests oogenesis at the pachytene stage of meiosis-1 in a DAF-16-dependent manner. We observe activated DAF-16-dependent deterioration of the somatic gonadal tissues like the sheath cells, and transcriptional de-regulation of the sperm-to-oocyte switch genes which may be the underlying reason for the absence of oogenesis. Deleting DAF-16 releases the arrest and leads to restoration of the somatic gonad but poor-quality oocytes are produced. Together, our study reveals the unrecognized cell non-autonomous interaction of Cyclin D/CYD-1 and FOXO/DAF-16 in the regulation of oogenesis and reproductive fidelity.